PROSPEK USAHA PEMBENIHAN IKAN MAS (Cyprinus carpio L) PADA UNIT PEMBENIH RAKYAT (UPR) DI KELURAHAN MENTAOS KECAMATAN BANJARBARU UTARA KOTA BANJARBARU PROPINSI KALIMANTAN SELATAN - Diah Puspitasari; Idiannor Mahyudin; Tri Dekayanti (Fish Scientiae, 2019)
The hatcheries operations of goldfish (Cyprinus carpio L) in Community Hatchery Unit at Mentaos Village in North Banjarbaru, Banjarbaru City, South Kalimantan Province have pretty good opportunity for its development since the comsumption of goldfish (Cyprinus carpio L) is increasing each year. The continous availability of goldfish (Cyprinus carpio L ) seeds and the fish farmer’s experience have developed a lot as well as support from local government by providing capital for sustainable development of goldfish (Cyprinus carpio L.)The research was done in Mentaos Village, North Banjarbaru District in Banjarbaru City of South Kalimantan Province. Primary and secondary data were gathered. The research conducted in order to analyse the prospect of goldfish seeding process in Community Hachery Unit (UPR) which include : (1) the profit, (2) BreakEven Point (BEP) analysis, (3) the feasibility of the business namely (R/C Ratio) and Payback Period (PP), (4) the analysis of market prospect and (5) marketing channels.The research show the profit achieved in the seeding gold fish (Cyprinus carpio, L) business in Mentaos Village is by average Rp.13.754.922,00/year, Break Even Point(BEP) by minimum selling price is Rp.86,94 per head and producing by minimum of 200.701 head year. Based on the feasibility of the business it is found that R/C Ratio of the fish hatchery operations in a single season production is 2,17(R/C>1), mean while Payback Period (PP) is 0,244 year or 2 month 29 days, the demand of goldfish (Cyprinuscarpio L) is bigger than the supply (D>S), it means the production still cannot fulfil the market demand and the marketing channels which allows the fish farmers to sell their product directly to the last consumer which become the most efficiency way.